The Extent of Jordanian Banks Commitment in Applying the Principles of Corporate Governance - Al Hanini, Eman (Asian Economic and Financial Review, 2014)
This study aimed to reveal the extent of Jordanian banks’ commitment to apply the principles of corporate governance. And to achieve this objective , a questionnaire was designed and distributed to a sample consisted of 120 respondents of the general managers’ assistants, managers of the administrations , managers of the branches, the assistants of the managers of the branches and the employees of the audit departments in the Jordanian banks. After data was analyzed using SPSS, the study concluded that the Jordanian banks are committed to apply the principles of the corporate governance regarding protecting the rights of the stakeholders and the shareholders and treating them fairly. Moreover, the Jordanian banks are committed to issue systems that determine the powers of the Board of Directors and its executive administration and its responsibilities. And the members of the board of directors in the Jordanian banks committed to the rules and the ethics of the professional functional work, to the disclosure and the transparency of the information published and to fulfill their social responsibilities towards the community. The study recommended the necessity of the control and supervision authorities to encourage all the banks to follow the approach of the banks regarding their commitment to the principles of the corporate governance regarding the social responsibility, and the necessity of establishing a private committee of the governance named the committee of corporate governance that cares of planning, revising and controlling the operations of the governance. Moreover, the necessity to make corrections whenever there is a need.